APPLICATION OF MULTIVARIATE ANALYSIS TO IDENTIFY DROUGHT TOLERANCE GENOTYPES OF MAIZE - & Kadhem, Ahmed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
In order to identify maize (Zea mays L.) genotypes had tolerate drought, Seven drought indices and 18 maize genotypes were used, to determine the efficiency of theses indices to identify tolerant and susceptible genotypes, Also interpretation the relationship between these indices using principle component , cluster of multivariate analysis and rank-sum method. The results indicated that MP, GMP, and STI were positively and significant correlated with Yp and Ys. Therefore, these indices have the potential to identify genotypes own well performance to stress and non-stress conditions. Screening drought tolerant genotypes using these indices discriminating G8 (Zm32*Zm60) G2 (Zm69*Zm49), G (Zm60*Zm61), and G11 (Zm49*Zm60) in spring season; and G8 (Zm32*Zm60) G2(Zm69*Zm49 ), G15 (Zm49*Zm19) and G18 (Zm60*Zm51) for autumn season as tolerant genotypes and have a higher potential productivity under stress and non-stress conditions.